GANGGUAN BERBAHASA PADA TOKOH SHAHIDA DALAM FILM “BAJRANGI BHAIJAAN” (KAJIAN PSIKOLINGUISTIK) - Alya Maulidia Zahra (STKIP PGRI SUMENEP, 2022)
This study aims to determine the language disorders of Shahida's character in the film